Effectiveness of temporary deafferentation of the arm on somatosensory and motor functions following stroke: a systematic review. (December 2016) - Opsommer, Emmanuelle; Zwissig, Camille; Korogod, Natalya; Weiss, Thomas
EXECUTIVE SUMMARY: Background: After stroke, regaining functional use of the upper limb can be challenging. Temporary deafferentation (TD) is a novel approach used in neurorehabilitation to voluntarily reduce the somatosensory input in a body part by temporary anesthesia; which has been shown to improve sensorimotor functions in the affected limb. Objectives: The primary objective of this systematic review was to present the best available evidence related to the effects of TD of the affected arm on the recovery of motor function and activity of the upper limb (arm and hand) following stroke. Further, this review aimed to assess the effects of TD on sensory function, activities of daily living (ADL) and quality of life following stroke, the acceptability and safety of the intervention as well as adverse events. Inclusion criteria Types of participants : Adult patients (18 years and older) with a clinical diagnosis of stroke, either hemorrhagic or ischemic. Types of interventions : Reports of rehabilitation that included the use of a pneumatic tourniquet, regional anesthesia or nerve block to achieve TD of an arm, or the use of TD as a stand-alone intervention. Outcomes : Primary outcomes were motor function and activity of the upper limb using assessment scales, motor tests and global motor functions. Secondary outcomes included measures of sensory function, ADL, impact of stroke and quality of life and pain. Additional outcomes were neurophysiological changes as studied with functional magnetic resonance imaging, magnetoencephalography and/or transcranial magnetic stimulation. Acceptability and safety of the intervention as well as adverse events were also included. Types of studies : We included any experimental and epidemiological studies. There were no randomized controlled trials. We included non-randomized controlled trials, quasi-experimental, before and after studies and case-control studies. Search strategy: We searched for both published and unpublished studies in major databases and all reference lists of relevant articles in English, German or French languages. We included studies published from January 1980 to October 2015. Data extraction: Data were extracted from included studies using a standardized data extraction tool from the Joanna Briggs Institute. Data synthesis: There was heterogeneity in the types of intervention and outcome measures, therefore statistical pooling of the findings was not appropriate. As such, the studies were grouped according to type of outcome where possible. Findings are presented in a narrative form. Results: Eight studies met the eligibility criteria. All outcome parameters related to the primary outcome (motor function and activity of the more affected upper extremity) showed an improvement during or after TD. The sensory functions significantly improved during or after TD when measured either by the grating orienting task or the grating orientation accuracy, and slightly improved when measured using the von Frey hair testing during TD. Conclusion: There is evidence supporting the use of TD of the upper extremity in adults after stroke. Temporary deafferentation can be recommended (Grade B).